2022
DOI: 10.1177/11772719221125123
|View full text |Cite
|
Sign up to set email alerts
|

Serum ACE2 Level is Associated With Severe SARS-CoV-2 Infection: A Cross-Sectional Observational Study

Abstract: Objectives: Angiotensin-converting enzyme 2 (ACE2) represents the primary receptor for SARS-CoV-2 to enter endothelial cells, causing coronavirus disease of 2019 (COVID-19). In this study, we investigate the association between circulating ACE2 levels with the severity of COVID-19. Methods: Serum ACE2 levels were measured in 144 COVID-19-positive subjects at hospital admission, and 123 COVID-19-negative control subjects. The association between ACE2 and clinical outcomes was analyzed. Results: About 144 COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Also, Hani et al carried out a cross-sectional observational study on the association between serum sACE2 levels with the severity of COVID-19. They demonstrated that serum sACE2 levels did not change among SARS-CoV-2-positive and negative groups [ 33 ]. In addition, another study by Kintscher et al reported that sACE2 levels and the Ang II/Ang I peptide ratio did not change in COVID-19 patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Also, Hani et al carried out a cross-sectional observational study on the association between serum sACE2 levels with the severity of COVID-19. They demonstrated that serum sACE2 levels did not change among SARS-CoV-2-positive and negative groups [ 33 ]. In addition, another study by Kintscher et al reported that sACE2 levels and the Ang II/Ang I peptide ratio did not change in COVID-19 patients [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increased lysis of mACE2-expressing cells as a result of severe infection could explain the possible causes of increased serum sACE2 levels in critically ill/deceased patients compared to mild or non-severe patients. Measurement of serum sACE2 in COVID-19 patients admitted to the hospital and control subjects showed that sACE2 serum levels were markedly greater in more severe and non-survivor cases of COVID-19 than in the milder patients [ 43 ]. Therefore, some studies have suggested that sACE2 can be used as a possible predictor marker of COVID-19 severity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation